Origin of fine‐scale wind stress curl structures in the Benguela and Canary upwelling systems. Issue 11 (24th November 2014) - Desbiolles, F.; Blanke, B.; Bentamy, A.; Grima, N.
Abstract Numerous studies have shown the primary importance of wind stress curl in coastal upwelling dynamics. The main goal of this new analysis is to describe the QuikSCAT surface wind stress curl at various scales in the Benguela and Canary upwelling systems. The dominant spatial pattern is characterized by cyclonic curl near continental boundaries and anticyclonic curl offshore, in association with equatorward alongshore (upwelling favorable) wind stress. At a smaller scale, we demonstrate the sensitivity of the QuikSCAT wind stress curl to coastal processes related to sea surface temperature (SST) mesoscale fluctuations by presenting a linear relationship between the curl and crosswind SST gradients. Despite the spatial and temporal sensitivity of the underlying thermal coupling coefficient, a local analysis of the fraction of the curl ascribed to SST variability shows that SST is a main driver of the wind stress curl variability and magnitude over the upwelling extension zone (∼100–300 km from the coast) in both the Canary and Benguela systems. Closer to the shore, the curl patterns derived from QuikSCAT observations are only loosely related to SST‐wind interactions. As a working hypothesis, they can also be associated with the coastline geometry and orographic effects that are likely to play an important role in local cooling processes.